2021
DOI: 10.1021/acsami.1c10957
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Reactions between the Electron Beam and Nanoparticle Capping Ligands with Correlative Fluorescence and Liquid-Phase Electron Microscopy

Abstract: Liquid-phase transmission electron microscopy (LP-TEM) enables real-time imaging of nanoparticle self-assembly, formation, and etching with single nanometer resolution. Despite the importance of organic nanoparticle capping ligands in these processes, the effect of electron beam irradiation on surface-bound and soluble capping ligands during LP-TEM imaging has not been investigated. Here, we use correlative LP-TEM and fluorescence microscopy (FM) to demonstrate that polymeric nanoparticle ligands undergo compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…48 Similar to the previous work, we utilized lower metal : ligand ratios than solution chemical synthesis to scavenge hydroxyl radicals that can oxidize metals and desorb ligands via oxidative elimination. 48,65,66 Solution pH can be affected by the electron beam due to production of hydronium ions; however, prior models have shown the pH is not significantly reduced for the low pH of the precursor solution ( pH ≈ 4). 67 Despite these differences, the qualitative processes that occur during reduction by NaBH 4 and aqueous electrons are expected to be similar.…”
Section: Resultsmentioning
confidence: 99%
“…48 Similar to the previous work, we utilized lower metal : ligand ratios than solution chemical synthesis to scavenge hydroxyl radicals that can oxidize metals and desorb ligands via oxidative elimination. 48,65,66 Solution pH can be affected by the electron beam due to production of hydronium ions; however, prior models have shown the pH is not significantly reduced for the low pH of the precursor solution ( pH ≈ 4). 67 Despite these differences, the qualitative processes that occur during reduction by NaBH 4 and aqueous electrons are expected to be similar.…”
Section: Resultsmentioning
confidence: 99%
“…46 Similarly, we utilized lower metal:ligand ratios than solution chemical synthesis because our previous work demonstrated that excess ligand was required to scavenge oxidizing hydroxyl radicals that can preferentially oxidize some metals and desorb ligands via oxidative elimination. 43,65,66 (diffusion limited) to 𝑑~𝑡 1/2 (reaction limited). 67 Prior in situ small angle x-ray scattering (SAXS) revealed similar linear increases in particle diameter with time during aggregative growth of gold nanoparticles by NaBH4 reduction of aqueous gold chloride.…”
Section: Electrospray Ionization Mass Spectrometry (Esi-ms) Of Mpeg-s...mentioning
confidence: 99%
“…at the nano-meter scale in wet-chemical environments [1][2][3]. Besides the uncontested benefits, such as high spatial resolution of TEM [4], utilising electrons for imaging caused several challenges to arise [5][6][7][8]. The main issue of using highenergy electrons for imaging is the inevitable creation of radiation damage in the irradiated matter, with radiolysis of water molecules being the most relevant in LP-TEM [3].…”
Section: Introductionmentioning
confidence: 99%